PERBEDAAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) DAN SNOWBALL THROWING DITINJAU DARI HASIL BELAJAR SISWA KELAS 5 SD - Arindra Ikhwan Nur Huda; Mawardi ,; Suhandi Astuti (Jurnal Karya Pendidikan Matematika, 2018)
ABSTRACT :The purpose of this study was to investigate the differences of Number Head Together and Snowball Throwing learning method types reviewed from the fifth grades of Elementary School in Ki HajarDewantoro learning outcomes in Mathematic. The type of the research is quasi research. The variable of the study was free variable which were Number Head Together (X1) and Snowball Throwing (X2) learning types and The bound variable used in the study was the students’ Mathematic learning outcomes. The analysis technique used in the study were the descriptive technique and statistical analysis with ANCOVA Test. The result of ANCOVA Test are Fcount is 5,398 and the significant is 0,0230. It indicatest that the probability is 0,023 is less than 0,05 so it means that the impact of the NHT learning method types is more higher significant than Snowball Throwing learning method types. Keyword :Number Head Together learning method, snowball throwing learning method, learning outcomes.